Apprentissages en profondeur et rencontres sociales dans un cours à distance - Nicole Racette; Bruno Poellhuber; Terry Anderson; Caroll-Ann Keating; Sirléia Rosa (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In order to support a better understanding of the subject matter and to favor peer support among students, softwares were introduced in accounting management, a distance education course offered by Téluq to 35 students. The softwares introduced include ‘Xmind’ for creating knowledge cards, the social software ‘Elgg’ and the videoconferencing software ‘Enjeux’. Although we observed 47 publications generated with the social software, used to exchange knowledge maps created with the ‘Xmind’ software, no group meetings to create knowledge maps were held by videoconference. Some of the students involved say that the construction of knowledge maps encouraged significant learning. But for several participants, time seems to have been the principal constraint for undertaking such an activity. Therefore, the objectives (deeper learning and cooperation) were achieved for some, but not for others.